A Novel Multiple Biomarker Panel for the Early Detection of High-grade Serous Ovarian Carcinoma - Han, Chanhee (Gynecol Oncol, 2018)
INTRODUCTION: Since the majority of patients are diagnosed at an advanced stage, ovarian cancer remains the most lethal gynecologic malignancy. There is no single biomarker with the sensitivity and specificity required for effective cancer screening; therefore, we investigated a panel of novel biomarkers for the early detection of high-grade serous ovarian carcinoma. METHODS: Twelve serum biomarkers with high differential gene expression and validated antibodies were selected: IL-1Ra, IL-6, Dkk-1, uPA, E-CAD, ErbB2, SLPI, HE4, CA125, LCN2, MSLN, and OPN. They were tested using Simple Plex , a multi-analyte immunoassay platform, in samples collected from 172 patients who were either healthy, had benign gynecologic pathologies, or had high-grade serous ovarian adenocarcinomas. The receiver operating characteristic (ROC) curve, ROC area under the curve (AUC), and standard error (SE) of the AUC were obtained. Univariate ROC analyses and multivariate ROC analyses with the combination of multiple biomarkers were performed. RESULTS: The 4-marker panel consisting of CA125, HE4, E-CAD, and IL-6 had the highest ROC AUC. When evaluated for the ability to distinguish early stage ovarian cancer from a non-cancer control, not only did this 4-marker panel (AUC=0.961) performed better than CA 125 alone (AUC=0.851; P=0.0150) and HE4 alone (AUC=0.870; P=0.0220), but also performed significantly better than the 2- marker combination of CA125+HE4 (AUC=0.922; P=0.0278). The 4-marker panel had the highest average sensitivity under the region of its ROC curve corresponding to specificity ranging from 100% down to ~95%. CONCLUSION: The four-marker panel, CA125, HE4, E-CAD, and IL-6, shows potential in detecting serous ovarian cancer at earlier stages. Additional validation studies using the biomarker combination in ovarian cancer patients are warranted.